2016
DOI: 10.1016/j.jad.2015.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of depression recovery in HIV-infected individuals managed through measurement-based care in infectious disease clinics

Abstract: Background Treatment of comorbid chronic disease, such as depression, in people living with HIV/AIDS (PLWHA) increasingly falls to HIV treatment providers. Guidance in who will best respond to depression treatment and which patient-centered symptoms are best to target is limited. Methods Bivariable analyses were used to calculate hazard ratios for associations between baseline demographic, mental health-related, and HIV-related factors on time to first depression remission among PLWHA enrolled in a randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…We constructed three models: (1) estimating the prevalence ratio of sustained viral suppression for those with any versus no depression, (2) estimating the prevalence ratio of sustained viral suppression for those with untreated depression or treated depression separately versus no depression, and (3) estimating the prevalence ratio of sustained viral suppression for those with treated versus untreated depression. Each model was adjusted for gender [30,31], race [31,32], homelessness [33,34], health insurance status [35,36], drug use [15,37], and time since HIV diagnosis [38,39]. In all multivariable analyses we included variables as potential confounders that were a priori and statistically determined to be significantly associated with any depression and sustained viral suppression (p ≀ 0.05).…”
Section: Analytic Methodsmentioning
confidence: 99%
“…We constructed three models: (1) estimating the prevalence ratio of sustained viral suppression for those with any versus no depression, (2) estimating the prevalence ratio of sustained viral suppression for those with untreated depression or treated depression separately versus no depression, and (3) estimating the prevalence ratio of sustained viral suppression for those with treated versus untreated depression. Each model was adjusted for gender [30,31], race [31,32], homelessness [33,34], health insurance status [35,36], drug use [15,37], and time since HIV diagnosis [38,39]. In all multivariable analyses we included variables as potential confounders that were a priori and statistically determined to be significantly associated with any depression and sustained viral suppression (p ≀ 0.05).…”
Section: Analytic Methodsmentioning
confidence: 99%
“…31 In depressed PLWH, studies have shown that the presence of co-occurring psychiatric disorders is the norm rather than the exception, with more than half of those with depression also having at least one other psychiatric disorder. 1,5,6,28,[32][33][34] While evidence suggests that occurrence of drug use, panic disorder, or heavy alcohol use 27,30 is associated with disparities in HIV treatment outcomes, less is known about the impact of such co-occurrence on disparities in depression treatment. 32 Given the high burden of psychiatric comorbidities among PLWH, understanding how they affect disparities in depression treatment is crucial for improving mental health treatment and achieving improved health outcomes in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, studies are using routinely captured electronic medical record data to address questions such as the effect of depression treatment on clinical outcomes (Bengtson et al, 2016a; Sowa et al, 2016). Thus, it is important to be able to account for misclassification errors stemming from the use of electronic medical records.…”
Section: Discussionmentioning
confidence: 99%